Role of gamma knife radiosurgery in craniopharyngioma - Ashis Patnaik; Ashok Kumar Mahapatra (Indian Journal of Neurosurgery)
Craniopharyngiomas continue to be a challenge to manage, due to difficulty in complete excision and frequent recurrences. The management protocol remains controversial. They have a tendency to invade the normal brain tissues around them and due to their position in suprasellar region in close relationship with vital structures like optic apparatus, pituitary-hypothalamic axis, complete removal is often not feasible without causing serious morbidity and mortality. In this scenario, sub-total excision seems to be a better alternative, which is plagued by early and frequent recurrences. Radiotherapy has been used for increasing the progression free survival and to improve the overall quality of life. Recently Gamma knife radiosurgery has evolved as a promising technique of radiating the residual or recurrent tumor in a single session with great accuracy and precision. This helps in maximizing the radiation dose to the tumor with steep dose fall off to the surrounding tissue, and hence there is better control of the tumor and minimal radiation exposure to surrounding normal, vital brain tissues. We discuss the current strategies of Gamma knife treatment for craniopharyngioma and review the literature.